Correction to: Shrimp Lipids Inhibit Migration, Epithelial–Mesenchymal Transition, and Cancer Stem Cells via Akt/mTOR/c-Myc Pathway Suppression (Biomedicines, (2024), 12, 4, (722), 10.3390/biomedicines12040722) - Thepthanee, Chorpaka; Ei, Zin Zin; Benjakul, Soottawat; Zou, Hongbin; Petsri, Korrakod; Innets, Bhurichaya; Chanvorachote, Pithi (My University, 2024)
In the original publication [1], there was a mistake in Figure 4 as published. Specifically, there was an issue with duplicated subfigures in Figure 4C. Additionally, the β-actin bands in Figures 4 and 5 appeared similar, which may have resulted from an error during figure preparation. The corrected Figure 4 appears below. The authors state that the scientific conclusions are unaffected. This correction was approved by the Academic Editor. The original publication has also been updated.